Gateway to genetic exchange? DNA double‐strand breaks in the bdelloid rotifer Adineta vaga submitted to desiccation. (15th February 2014) - Hespeels, B.; Knapen, M.; Hanot‐Mambres, D.; Heuskin, A.‐C.; Pineux, F.; Lucas, S.; Koszul, R.; van Doninck, K.
Abstract The bdelloid rotifer lineage Adineta vaga inhabits temporary habitats subjected to frequent episodes of drought. The recently published draft sequence of the genome of A. vaga revealed a peculiar genomic structure incompatible with meiosis and suggesting that DNA damage induced by desiccation may have reshaped the genomic structure of these organisms. However, the causative link between DNA damage and desiccation has never been proven to date in rotifers. To test for the hypothesis that desiccation induces DNA double‐strand breaks (DSBs), we developed a protocol allowing a high survival rate of desiccated A. vaga. Using pulsed‐field gel electrophoresis to monitor genomic integrity, we followed the occurrence of DSBs in dried bdelloids and observed an accumulation of these breaks with time spent in dehydrated state. These DSBs are gradually repaired upon rehydration. Even when the genome was entirely shattered into small DNA fragments by proton radiation, A. vaga individuals were able to efficiently recover from desiccation and repair a large amount of DSBs. Interestingly, when investigating the influence of UV‐A and UV‐B exposure on the genomic integrity of desiccated bdelloids, we observed that these natural radiations also caused important DNA DSBs, suggesting that the genome is not protected during the desiccated stage but that the repair mechanisms are extremely efficient in these intriguing organisms.